1883 Tenn. Pub. Acts 17, A Bill to Be Entitled An Act to Prevent the Sale, Loan or Gift of Pistol Cartridges in This State, ch. 13. - (:unkn) unknown (General Publisher, 1883)
[I]t shall be unlawful for any person or persons to buy or sell or give away any pistol cartridges in this state.
--
Keywords: TRANSFER ONLY